P178 Sinus rhythm restoration by catheter ablation improved cognitive function in elderly patients with atrial fibrillation. (13th January 2020) - Fujiyoshi, K; Minami, M; Saito, D; Hashimoto, T; Yoshizawa, T; Oikawa, J; Tojo, T; Yamaoka-Tojo, M; Ako, J
Abstract: Background: Atrial fibrillation (AF) may cause cognitive impairment. However, the impact of sinus rhythm (SR) restoration by catheter ablation on the improvement of cognitive function remains to be elucidated. Methods: A total of 57 consecutive elderly patients (70.8 ± 4.8 years old) who underwent catheter ablation for AF were prospectively enrolled. The change of cognitive function for 6 months was compared between patients with SR restoration (at least 3 months; n = 49) and patients with AF recurrence (n = 8). Cognitive function was evaluated by the mini-mental state examination (MMSE). Results: There was no significant difference in baseline characteristics between the 2 groups, including MMSE score (27.3 ± 2.6 vs. 27.6 ± 1.5 points; p = 0.793). The change of MMSE score was significantly greater in patients with SR restoration than those with AF recurrence (0.28 ± 0.70 vs. − 0.50 ± 0.75 points; p = 0.006; Figure). The general liner modeling revealed that SR restoration (effect estimate, 0.369; 95% confidence interval, 0.110 to 0.627; p = 0.006) was independently associated with the change of MMSE score. Conclusion: In elderly AF patients, successful restoration of SR by catheter ablation was associated with the improvement of cognitive function.